Tourism management an introduction - Inkson, Clare; Minnaert, Lynn (Los Angeles SAGE, 2022)
This introductory text provides readers with a robust understanding of tourism and its industries, including how destinations are developed, marketed and managed, and how tourism impacts communities, environments and economies. The authors discuss the critical issues affecting 21st century tourism, such as sustainability, the climate crisis, globalisation, community, technology, the environment and the sharing economy. The text has been fully updated in light of the Covid-19 pandemic and its notable, and in some cases lasting, impacts on the tourism industry.

"The text features new mini-case studies (snapshots) and international case studies from countries around the globe including USA, Saudi Arabia, India, China, New Zealand, Australia, Namibia and the UK. It discusses the latest trends in transport, hospitality, attractions and the travel trade and includes examples from major tourism companies including Trip.com, TUI and Airbnb.

The book is suitable for students who are starting their tourism studies as part of their college or university education." --
Part I: Tourism Overview -- Chapter 1. Introduction -- Chapter 2. Understanding Tourism -- Part II: Tourism Supply and Demand -- Chapter 3. Tourist Generating Regions -- Chapter 4. Tourism Demand -- Chapter 5. Tourism Suppliers -- Chapter 6. Intermediaries in the Tourism System -- Part III: Tourism Impacts -- Chapter 7. The Economic Impacts of Tourism -- Chapter 8. The Social and Cultural Impacts of Tourism -- Chapter 9. The Environmental Impacts of Tourism -- Part IV: Tourism Management and Marketing -- Chapter 10. Destination Development and Management -- Chapter 11. Tourism Marketing -- Chapter 12. The Management of Visitors -- Chapter 13. Public Sector Involvement in Tourism -- Part V: Tourism Ahead -- Chapter 14. Tourism and the Future.
Includes bibliographical references and index.
Keywords: Tourism; Tourism -- Management